Acute chest pain in a triathlete: rupture of the noncoronary sinus of Valsalva into the right ventricle - Zhu, Ernan; Westenfeld, Ralf; Gastl, Mareike; Bönner, Florian; Assmann, Alexander; Nia, Amir M.; Kelm, Malte; Jung, Christian (Journal of Thoracic Disease, 2016)
Sinus of Valsalva (SoV) aneurysm is a rare cardiac disease which can be congenital or acquired. A ruptured SoV aneurysm presents a clinical emergency and can lead to progressively deteriorating heart failure. Therefore, appropriate treatment requires prompt and accurate diagnosis. Most ruptured or nonruptured SoV aneurysms are diagnosed by the means of echocardiography. However, cardiovascular magnetic resonance (CMR) can provide information on precise anatomy and mechanisms due to its excellent soft tissue contrast and high resolution, and thereby allows for optimized preoperative planning of the repair strategy. In the present case, we demonstrate the benefit of CMR in emergency settings.